Pengaruh Ketidakpastian Ekonomi Terhadap Stabilitas Likuiditas Pada Bank Umum Syariah di Indonesia - Raqiqah Ramiyanti; Devina Restu Siningsih; Yani Aguspriyani (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of economic uncertainty on liquidity stability in Islamic commercial banks in Indonesia. Economic uncertainty is proxied by inflation, while liquidity stability is measured using the Financing to Deposit Ratio. This research uses a quantitative associative approach with secondary data obtained from official publications of Bank Indonesia and the Financial Services Authority. The observation period covers 2020 to 2025 using quarterly time series data. The data were analyzed using STATA through descriptive statistics, time series analysis, simple linear regression, and classical assumption tests. The results show that inflation has a negative relationship with the Financing to Deposit Ratio, as indicated by a regression coefficient of -0.6586246. This means that an increase in inflation tends to reduce the Financing to Deposit Ratio of Islamic commercial banks. However, the probability value of 0.170 is higher than the significance level of 0.05, indicating that inflation does not have a statistically significant effect on liquidity stability. The coefficient of determination of 0.0922 shows that inflation explains only 9.22 percent of the variation in the Financing to Deposit Ratio, while the remaining 90.78 percent is influenced by other factors outside the research model. These findings indicate that the liquidity stability of Islamic commercial banks is not primarily determined by inflation, but also by internal banking factors and other macroeconomic conditions